2018
DOI: 10.1002/ejlt.201700528
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Evaluation Index for Predicting the Degradation Rate of Frying Oils Based on Their Fatty Acid Composition

Abstract: The changes in the fatty acid composition of eleven edible oils (soybean, rapeseed, natural and refined sesame, corn, safflower, olive, rice bran, natural and refined perilla, coconut) are investigated during deep frying. French fries are intermittently fried for 5 h each day for 6 consecutive days at 180 °C in these oils. The results suggested that all of the oils contained large amounts of unsaturated fatty acids (83.49–95.28%) before deep frying, except for coconut oil (7.13%). With the extension of frying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…His research was all carried out at 120 °C with an automatic Rancimat apparatus, which was close to theoretical autoxidation experimental conditions. Different from his research, our research was conducted under real frying conditions at 180 °C, which was very close to the actual frying process in life. It is acceptable if the results are different due to different experimental conditions.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…His research was all carried out at 120 °C with an automatic Rancimat apparatus, which was close to theoretical autoxidation experimental conditions. Different from his research, our research was conducted under real frying conditions at 180 °C, which was very close to the actual frying process in life. It is acceptable if the results are different due to different experimental conditions.…”
mentioning
confidence: 87%
“…We thank Dr. Albert Dijkstra (the author of the preceding Letter to the Editor) for his interest in the publication “A Novel Evaluation Index for Predicting the Degradation Rate of Frying Oils Based on Their Fatty Acid Composition,” which developed a novel index to predict the unsaturated fatty acid degradation rate of a variety of unsaturated fatty acid‐based oils during deep frying.…”
mentioning
confidence: 99%
“…It would enable users to choose the most stable frying oils and guide producers in their development of more stable oils. It is therefore with great interest that I studied the article by Liu et al because it claims to provide a novel evaluation index for frying oils that only takes their fatty acid composition into account. Another reason that I studied the article with great interest is that some 20‐odd years ago, I wrote a paper that also correlates the stability of an oil to its fatty acid composition.…”
mentioning
confidence: 99%
“…Liu et al . on the other hand concluded that “the ratio of palmitic to oleic acid in the oils before deep frying has an important impact on the degradation of a variety of unsaturated fatty acid based oils, and can be used as an evaluation index for predicting the degradation rate of such oils before deep frying.” Now, it could be that this ratio is a roundabout way of expressing the polyunsaturated content of the various oils, but studying the paper by Liu et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation